Correlation between Leukocyte Esterase Levels and Pregnancy Latency Interval in Pregnant Women with a History of Preterm Premature Rupture of Membranes - Andayani, Aviasti Pratiwi; Bayuaji, Hartanto; Siddiq, Amillia (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Introduction: Bacterial colonization of the vagina and cervix can lead to intra amniotic infections that increase the risk of chorioamnionitis, premature rupture of membranes, and preterm labor. Leukocyte esterase (LE) is an alternative test that is affordable and easy to perform to predict the risk of preterm labor due to urinary tract infection. We examined the correlation between leukocyte esterase levels and gestational latency interval in pregnant women with preterm premature rupture of membranes.Methods: This study is an observational study with a cross-sectional design from the medical records of singleton pregnancy patients with preterm premature rupture of membranes undergoing conservative treatment at Dr. Hasan Sadikin General Hospital, Bandung. Researchers analyzed the difference in mean latency interval and the correlation between leukocyte esterase levels and latency interval. The data processing results regarding the correlation between variables are presented in tables and graphs.Results: Of 101 patients, 76 patients met the inclusion criteria; 26 patients (34%) had negative results for leukocyte esterase examination, while 50 patients (66%) were positive. The average latency period of all patients was 2.16 days. The latency period ≤2 days occurred in 53% of patients, with the shortest latency period found in patients with leukocyte esterase +4 levels (1.5 days). Moreover, the ANOVA test results show that the correlation between the age latency period and leukocyte esterase levels obtained a value of f-ratio =1.44 with a p-value of 0.65, indicating no significant results at p<0.05.Conclusion: This study found no significant correlation between leukocyte esterase levels and the latency interval after preterm premature membrane rupture.Hubungan antara Kadar Leukosit Esterase dan Interval Masa Latensi Kehamilan pada Ibu Hamil dengan Riwayat Ketuban Pecah Dini pada Kehamilan PrematurAbstrakPendahuluan:Penjalaran infeksi bakteri dari kolonisasi bakteri pada vagina dan serviks menyebabkan infeksi intraamniotik yang meningkatkan risiko korioamnionitis, ketuban pecah dini, serta persalinan prematur. Penapisan infeksi saluran kemih (ISK) melalui pemeriksaan kadar leukosit esterase (LE) merupakan alternatif pemeriksaan yang terjangkau dan mudah dilakukan untuk mencegah persalinan prematur. Penelitian ini meneliti hubungan antara kadar leukosit esterase dan masa latensi kehamilan pada ibu hamil dengan ketuban pecah dini <34 minggu.Metode: Penelitian ini merupakan studi observasional dengan desain cross-sectional dari rekam medik pasien hamil tunggal dengan ketuban pecah dini <34 minggu yang menjalani perawatan konservatif di RSUP Dr.Hasan Sadikin Bandung. Kriteria eksklusi pada penelitian ini ialah penyulit lain pada ibu dan janin dan pemberian tokolitik. Peneliti menganalisis perbedaan rerata masa latensi serta hubungan kadar leukosit esterase dengan masa latensi kehamilan pada ketuban pecah dini <34 minggu. Hasil olah data mengenai hubungan antar variabel disajikan dalam bentuk tabel dan grafik.Hasil: Dari 101 pasien, terdapat 76 pasien yang memenuhi kriteria inklusi, didapatkan hasil pemeriksaan leukosit esterase negatif sebanyak 34% (26 pasien), dan positif pada 66% pasien (50 pasien). Rerata masa latensi dari seluruh pasien ialah 2,16 hari. Masa latensi ≤ 2 hari terjadi pada 53% pasien dengan masa latensi paling singkat didapatkan pada pasien dengan kadar leukosit esterase +4 yaitu 1,5 hari. Pada uji Anova hubungan rerata masa latensi dengan kadar leukosit esterase didapatkan nilai rasio-f = 1,44 dengan nilai p 0.65 yang menunjukkan hasil tidak signifikan pada p<0.05.Kesimpulan: Hasil penelitian menunjukkan tidak ada korelasi signifikan antara kadar leukosit esterase dengan lama masa latensi kehamilan setelah ketuban pecah dini <34 minggu.Kata kunci: Infeksi saluran kemih; leukosit esterase; ketuban pecah dini; masa latensi